Analisis Produksi Dan Pendapatan Usaha Budidaya Kepiting Soka (scylla sp) di Kecamatan Sei Lepan Kabupaten Langkat - Nasution, Irwanta; Ginting, Rahmanta; Siregar, M. Akbar (Universitas Medan Area, 2014)
The aim of this research into analysis production factors to production level and to analysis conducting operating revenues crab culture (Scylla sp) at Sei Lepan Sub-district in Langkat District. Method that is utilized is logistic production Cobb Douglass and data that is utilized is crab farmer production and income data up to a year 2012. Analysis result Cobb Douglass point out that logistic model estimation production which is: Ln Prod = 0,040 + 0,022 Ln Ll – 0,102 Ln Tkdk + 0,005 Ln Tklk + 0,995 Ln Bb. Its outgrows appreciative Return to Scale (RTS) are 0,92. So RTS< 1 (Decreasing return to scale). Determinant coefficient 0,990 explain that percentage of independent variable regard dependent's variable as big as 99,0% and hypothesis that declares for that variable stocks down and far ranging positive ascendant farm and signifikan to soft shell crab production (Scylla sp) accepted. Income average crab farmer soft shell crab (Scylla sp) year long production as big as Rp. 11.709.511,- . Mean while of arithmetic average R / C ratio crab aquaculture effort soft shell crab is gotten = 1,10 its means that effort is reasonable to be carried on. Keyword : crab (Scylla sp), production, income, Cobb Douglass